Soil slope remediation works using soil nail - Chang, Teck Leong, 1977-, author 620784 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Thesis (Sarjana Kejuruteraan (Geoteknik)) - Universiti Teknologi Malaysia, 2019